The children’s story: a facilitator of thinking from a pedagogical experience (2014)
This reflective article is a preview of a research developed in the Master’s degree in Education, concerning to the promotion of inquiry through a pedagogical experience that used the children’s story called “The little shepherdess” by Rafael Pombo, set to music by Carlos Vives, and illustrated by Lorenzo Jaramillo. The academic exercise aimed at stimulating thinking and was carried out with six five-year-old girls who studied at Comfaboy Social Kindergarten of Toca municipality. The conceptual basis uses key aspects from the History of Childhood, children’s literature and thinking, by analyzing how thinking is transformed as a teaching strategy in the education of the individual. Methodologically speaking, it is based on the promotion of learning, keeping in mind cooperation, with pedagogical actions interesting for children and parents that develop social skills and thinking. Likewise, it included the use of instruments such as direct observation and field journals written up during the work sessions. The paper ends up with a discussion on the results based on an analysis matrix.